Seismicity properties of the chain transform fault inferred using data from the PI-LAB experiment - Leptokaropoulos, K; Rychert, CA; Harmon, N; Kendall, JM (Wiley, 2023)
Oceanic transform faults are intriguing in that they do not produce earthquakes as large as might be expected given their dimensions. We use 1-year of local seismicity (370 events above MC = 2.3) recorded on an array of ocean bottom seismometers (OBSs) and geophysical data to study the seismotectonic properties of the Chain transform, located in the equatorial Mid-Atlantic. We extend our analysis back in time by considering stronger earthquakes (MW ≥ 5.0) from global catalogs. We divide Chain into three areas (east, central, and west) based on historical event distribution, morphology, and multidimensional OBS seismicity cluster analysis. Seismic activity recorded by the OBS is the highest at the eastern area of Chain where there is a lozenge-shaped topographic high, a negative rMBA gravity anomaly, and only a few historical MW ≥ 5.5 events. OBS seismicity rates are lower in the western and central areas. However, these areas accommodate the majority of seismic moment release, as inferred from both OBS and historical data. Higher b-values are significantly correlated with lower rMBA and with shallower bathymetry, potentially related to thickened crust. Our results suggest high lateral heterogeneity along Chain. Patches with moderate to low OBS seismicity rates that occasionally host MW ≥ 6.0 earthquakes are interrupted by segments with abundant OBS activity but few historical events with 5.5 ≤ MW < 6.0. This segmentation is possibly due to variable fluid circulation and alteration, which may also change in time.